Operando Spatial Pressure Mapping Analysis for Prototype Lithium Metal Pouch Cells Under Practical Conditions - Kyobin Park; Myungjae Lee; Jongchan Song; A. Reum Ha; Seongmin Ha; Seunghyeon Jo; Juyeop Song; Seung Hyun Choi; Wonkeun Kim; Kyunghan Ryu; Jaewook Nam; Kyu Tae Lee (Advanced Science, 2023)
Abstract Monitoring and diagnosing the battery status in real‐time are of utmost importance for clarifying failure mechanism, improving battery performance, and ensuring safety, particularly under fast charging conditions. Recently, advanced operando techniques have been developed to observe changes in the microstructures of lithium deposits using laboratory‐scale cell designs, focusing on understanding the nature of Li metal electrodes. However, the macroscopic spatial inhomogeneity of lithium electroplating/stripping in the prototype pressurized pouch cells has not been measured in real‐time under practical conditions. Herein, a new noninvasive operando technique, spatial pressure mapping analysis, is introduced to macroscopically and quantitatively measure spatial pressure changes in a pressurized pouch cell during cycling. Moreover, dynamic spatial changes in the macroscopic morphology of the lithium metal electrode are theoretically visualized by combining operando pressure mapping data with mechanical analyses of cell components. Additionally, under fast charging conditions, the direct correlation between abrupt capacity fading and sudden increases in spatial pressure distribution inhomogeneity is demonstrated through comparative analysis of pouch cells under various external pressures, electrolyte species, and electrolyte weight to cell capacity (e/c) ratios. This operando technique provides insights for assessing the current battery status and understanding the complex origin of cell degradation behavior in pressurized pouch cells.